Tears and cheers: A narrative inquiry of a doctoral student’s resilience in study abroad - Wu, Xinxin (Frontiers in Psychology, 2022)
Existing literature has revealed many issues related to PhD students’ wellbeing, such as anxiety and stress, which are likely to cause PhD students attrition or dropout. As one of the key coping strategies against psychological burnout, resilience has received increasing attention among various teacher groups. However, it still lacks a systematic understanding in students, in particular PhD students. This article explores doctoral students’ resilience through a narrative inquiry of the resilience building process of a PhD student in language and linguistics, Hongxia, in the UK. Drawing on the research methods and results of resilience from teachers, this study examines Hongxia’s lived experience as a PhD student throughout her three years of learning and research, and uncovers the dynamic and multifaceted process of resilience building as the interplay between PhD students’ agency, peers, supervisors, academics, families and friends. The current research supports the value of narrative inquiry, in particular critical story analysis, as a tool for studying the resilience building processes in PhD students during their candidature. It also hopes to provide insight for administers, supervisors, and other related stakeholders on their intervention to support and facilitate the research journey of doctoral students.